High-permeability MOF (Metal Organic Framework) film as well as preparation method and application thereof

By depositing and calcining zinc carbonate nanosheets on the surface of the porous support and converting them into organic ligands, a high permeability MOF membrane was prepared, which solved the problem of low permeability caused by incomplete conversion of oxide layer in the prior art, and achieved Improved gas separation performance.

CN119318891AActive Publication Date: 2025-01-17NANJING TECH UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411401508.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-17
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

In the prior art, the preparation procedure of the metal oxide layer is complicated and leads to the inability to completely convert the dense oxide layer, introducing transfer resistance, resulting in low permeability and efficiency of the MOF film.

Method used

Zinc carbonate nanosheets were deposited on the surface of the porous support, and after calcination and organic ligand treatment, they were converted into MOF membranes to avoid pore seepage and form densely oriented MOF membranes.

Benefits of technology

The preparation of a high permeability MOF membrane is achieved, which significantly improves the gas separation effect, avoids pore seepage and membrane defects, and improves the separation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318891A_ABST
    Figure CN119318891A_ABST
Patent Text Reader

Abstract

The invention discloses a high-permeability MOF (Metal Organic Framework) film as well as a preparation method and application thereof. The preparation method comprises the following steps: 1) depositing a zinc carbonate nanosheet on the surface of a porous support body; 2) calcining the porous support to obtain a porous support with a zinc oxide nanosheet layer deposited on the surface; and 3) converting the zinc oxide nanosheet layer into the MOF film in the presence of an organic ligand on the porous support body to obtain the MOF film. According to the method, ultrathin zinc carbonate nanosheets are firstly deposited on the surface of a porous support body and then calcined, so that an ultrathin zinc oxide nanosheet layer which is loosely arranged and mechanically stable is formed on the surface of the porous support body, and the ultrathin zinc oxide nanosheet layer is used as a zinc source for synthesizing the MOF membrane and is placed in an organic ligand atmosphere to induce conversion of the zinc oxide nanosheet on the surface of the support body to the MOF membrane. The MOF membrane obtained by conversion has a compactly oriented membrane structure, and is free of leakage or filled in pores of a support body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a high-permeability MOF film and a preparation method and application thereof. Background Art

[0002] Metal Organic Framework (MOF) materials stand out for their diverse topologies and flexible and customizable host-guest chemistry. This provides a unique platform for MOF-based membranes to fine-tune nanochannels, including pore structures and specific interfacial interactions at the angstrom scale. As a result, microporous MOF membranes with carefully designed pore systems have been widely studied, showing high selectivity and high permeability in most gas separations. However, finding a balance between simple and sustainable manufacturing processes and the superior performance of the resulting MOF membranes remains an ongoing challenge.

[0003] The metal oxide conversion strategy - a synthetic strategy that fixes metal oxides (such as zinc oxide (ZnO)) as metal sources on a support and then activates them with organic ligands to form membranes - shows the potential for the simple preparation of MOF membranes. However, in the prior art, most reported metal oxide layers involve relatively complex preparation procedures, and the oxide layers obtained by these procedures inevitably show a certain degree of pore penetration, resulting in the inability to fully convert the dense oxide layer, thereby introducing additional transfer resistance, and ultimately resulting in low permeability and overall efficiency of the membrane for gas separation. Summary of the invention

[0004] In view of the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a high-permeability MOF film. The MOF film obtained by the preparation method does not have pore permeation phenomenon, has high permeability, and significantly improves the separation effect when used for gas separation.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a MOF film comprises the following steps: 1) depositing zinc carbonate nanosheets on the surface of a porous support; 2) calcining the porous support to obtain a porous support with a zinc oxide nanosheet layer deposited on the surface; 3) converting the zinc oxide nanosheet layer into a MOF film in the presence of an organic ligand to obtain the MOF film.

[0007] In some embodiments, in step 1), after the deposition, the thickness of the zinc carbonate nanosheets is 0.5 to 2 μm.

[0008] In some embodiments, in step 1), the deposition is achieved by vacuum filtering a dispersion of zinc carbonate nanosheets on a porous support.

[0009] In some embodiments, the molar concentration of zinc carbonate nanosheets in the dispersion is 0.04 to 0.2 mol·L -1 .

[0010] In some embodiments, the dispersed phase of the dispersion is selected from a combination of one or more of water, methanol, ethanol, and acetone.

[0011] In some embodiments, the preparation method further comprises the step of preparing zinc carbonate nanosheets by hydrothermal reaction using zinc oxide nanoparticles and sodium bicarbonate aqueous solution as raw materials.

[0012] In some embodiments, the zinc oxide nanoparticles have a particle size of 50 to 200 nm.

[0013] In some embodiments, the molar ratio of the zinc oxide nanoparticles to sodium bicarbonate is 1:1-3.

[0014] In some embodiments, the temperature of the hydrothermal reaction is 60-100°C.

[0015] In some embodiments, the hydrothermal reaction time is 2 to 5 hours.

[0016] In some embodiments, the zinc carbonate nanosheets have a lateral size of 1 to 10 μm and a thickness of 10 to 50 nm.

[0017] In some embodiments, the preparation method further comprises a step of vacuum drying before the calcination.

[0018] In some embodiments, in step 2), the calcination temperature is 300-500°C.

[0019] In some embodiments, in step 2), the calcination time is 2 to 3 hours.

[0020] In some embodiments, in step 2), the thickness of the zinc oxide nanosheet layer is 0.5-2 μm.

[0021] In some embodiments, in step 3), the organic ligand is selected from one or more combinations of imidazole, benzimidazole, 2-methylimidazole, 4,5-dichloroimidazole, 5-chlorobenzimidazole, 5-methylbenzimidazole and 2-aminobenzimidazole.

[0022] In some embodiments, in step 3), the conversion method is selected from a combination of one or more of solution heat treatment, steam heat treatment, and electrochemical treatment.

[0023] In some embodiments, the organic ligand exists in the form of a solution, and the concentration of the organic ligand in the solution is 1 to 3 mol / L.

[0024] In some embodiments, in step 3), a ligand regulator is further added, and the ligand regulator is selected from a combination of one or more of sodium formate, formic acid, acetic acid, and benzoic acid.

[0025] In some embodiments, the porous support is selected from porous alumina or porous silicon carbide.

[0026] In some embodiments, the porous support has a pore size of 0.2 to 5 μm and a porosity of 30 to 50%.

[0027] In some embodiments, the porous support is selected from one of a wafer, a single-channel tube, or a multi-channel tube.

[0028] In some embodiments, the MOF is selected from a combination of one or more of ZIF-7, ZIF-8, ZIF-62, ZIF-71, ZIF-95, and ZIF-302.

[0029] The present invention also provides a MOF film prepared by the above preparation method.

[0030] The present invention also provides use of the MOF film for gas separation.

[0031] Furthermore, the gas is selected from the group consisting of carbon dioxide / methane, carbon dioxide / nitrogen, ethylene / ethane, propylene / propane, and separation of hexane isomers.

[0032] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0033] The present invention deposits ultra-thin zinc carbonate nanosheets on the surface of a porous support, vacuum-dries and then heats to form a loosely arranged, mechanically stable ultra-thin zinc oxide nanosheet layer on the surface of the porous support, uses the nanosheet as a zinc source for synthesizing a MOF membrane, places the nanosheet in an organic ligand atmosphere, and induces the conversion of the zinc oxide nanosheets on the surface of the support into a MOF membrane. The converted MOF membrane has a densely oriented membrane structure, and does not leak or fill in the pores of the support.

[0034] The ultra-thin structure of the zinc oxide nanosheets used in the present invention and their loosely stacked state on the surface of the support body make them highly accessible and reactive, so that they can be completely converted in the process of being converted into a MOF membrane. At the same time, the zinc oxide nanosheets, as a precursor deposition material, can avoid the occurrence of pore permeation in the pores of the support body, so the prepared MOF membrane has high gas permeability, while the prior art uses zinc oxide nanosol or nanoparticles as a zinc source, which is prone to pore permeation, resulting in more membrane defects and insufficient separation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the zinc oxide nanosheet layer prepared in Example 1;

[0036] Figure 2 This is the XRD pattern of the zinc oxide nanosheet layer prepared by conversion in Example 1;

[0037] Figure 3 The surface and cross-sectional SEM images of the MOF film prepared in Example 1;

[0038] Figure 4 This is the EDS image of the MOF film prepared in Example 1;

[0039] Figure 5 The surface and cross-sectional SEM images of the MOF film prepared in Example 2;

[0040] Figure 6 XRD pattern of the MOF film prepared in Example 2;

[0041] Figure 7 The MOF film prepared in Example 2 <100> AFM images of orientation;

[0042] Figure 8 Surface and cross-sectional SEM images of the MOF film prepared in Example 3;

[0043] Fig. 9 XRD pattern of the MOF film prepared in Example 3;

[0044] Fig.10 This is a SEM image of the zinc oxide nanosheet layer prepared in Example 4;

[0045] Fig.11 Surface and cross-sectional SEM images of the MOF film prepared in Example 4;

[0046] Fig.12 This is a SEM image of the zinc oxide nanoparticle layer prepared in Comparative Example 1;

[0047] Fig.13 XRD pattern of the MOF film prepared in Comparative Example 1;

[0048] Fig.14 Surface and cross-sectional SEM images of the MOF film prepared in Comparative Example 1. DETAILED DESCRIPTION

[0049] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention, but the present invention is not limited to the scope of the examples.

[0050] Example 1

[0051] This embodiment provides a MOF film, and the preparation steps thereof are as follows:

[0052] Zinc carbonate nanosheets were prepared by hydrothermal reaction of zinc oxide nanoparticles (100 nm in diameter) and sodium bicarbonate aqueous solution as raw materials. The molar ratio of zinc oxide nanoparticles to sodium bicarbonate was 1:1, the reaction temperature was 100°C, and the reaction time was 2 h to obtain zinc carbonate nanosheets (5 μm in lateral size and 25 nm in thickness).

[0053] Take 0.01g of the above zinc carbonate nanosheets and disperse them in 2mL of water (0.04mol·L -1 ), and deposited on a porous alumina ceramic sheet by vacuum filtration to form a zinc carbonate nanosheet layer with a thickness of about 1 μm.

[0054] The alumina ceramic sheet deposited with the zinc carbonate nanosheet layer was placed in a muffle furnace and calcined for 2 hours at 35° C. to form loosely stacked zinc oxide nanosheet layers.

[0055] Figure 1 and Figure 2 The SEM and XRD patterns of the obtained zinc oxide nanosheets are shown. It can be seen that the zinc oxide nanosheets formed on the porous alumina ceramic sheet are pure phase zinc oxide nanosheets with a thickness of 1 μm.

[0056] 2.4283 g of 2-methylimidazole was ultrasonically dissolved in 16 mL of deionized water to prepare a ligand solution. Subsequently, an alumina ceramic sheet with a zinc oxide nanosheet layer of 1 μm thick was placed in a polytetrafluoroethylene reactor containing the above ligand solution and placed in a forced air drying oven at 80 ° C for 6 hours to promote the conversion of zinc oxide nanosheets into ZIF-8 membranes, and then naturally cooled. The ZIF-8 membrane produced by heat treatment of the 2-methylimidazole ligand solution was rinsed alternately with deionized water and methanol three times, and then soaked in fresh methanol for 12 hours to remove residual water molecules in the pores of the ZIF-8 membrane. Finally, the ZIF-8 membrane was dried at room temperature for 12 hours before structural characterization and gas permeation testing.

[0057] Figure 2 and Figure 3The XRD pattern and surface and cross-sectional SEM images of the ZIF-8 membrane prepared by the conversion of zinc oxide nanosheets are shown. It can be seen that the zinc oxide nanosheet layer has been completely converted into a highly crystalline ZIF-8 membrane. The surface of the membrane is dense and defect-free, with a thickness of 1μm. Figure 4 The EDS graphs shown show that there is no porosity in the ZIF-8 membrane layer. The ZIF-8 film exhibits excellent separation performance for propylene / propane (C3H6 / C3H8), with a permeation rate of about 200 GPU for propylene and a selectivity of about 80 for propylene / propane separation. This performance exceeds that of most ZIF-8 membranes prepared by zinc oxide conversion.

[0058] Example 2

[0059] The preparation of zinc oxide nanosheet layer is the same as that in Example 1.

[0060] Take 4.105g of 2-methylimidazole and dissolve it ultrasonically in 50mL of deionized water to prepare a ligand solution. Add 0.1mL of sodium formate to the ligand solution. Then place the alumina ceramic sheet (working electrode) and graphite electrode (reference electrode) deposited with the zinc oxide nanosheet layer in a 50mL electrolytic cell. Pour the prepared ligand solution into the electrolytic cell to ensure that the solution covers the porous alumina ceramic sheet. Then apply a constant current of 0.5mA for 60min. The applied constant current will promote the deprotonation of the ligand and attack the zinc oxide nanosheet to cause a point-to-point conversion to form a ZIF-8 membrane. After the conversion, the membrane cleaning, pore activation and drying steps are the same as in Example 1.

[0061] Figure 5 and Figure 6 The surface SEM images and cross-sectional XRD patterns of the ZIF-8 membrane prepared by electrochemically driven zinc oxide nanosheet conversion are shown in Figure 1. <100> The channels are oriented, and the membrane thickness is only 500nm, and there is no pore permeation phenomenon. Figure 7 show <100> The intergrowth of oriented ZIF-8 crystals results in a large roughness on the membrane surface. The ZIF-8 film exhibits excellent separation performance for ethylene / ethane (C2H4 / C2H6), with a permeation rate of about 130 GPU for ethylene and a selectivity of about 8.2 for propylene / propane separation. This performance exceeds the separation performance of most MOF membranes for ethylene / ethane.

[0062] Example 3

[0063] The preparation of zinc oxide nanosheet layer is the same as that in Example 1.

[0064] Take 3.105g of 2-methylimidazole powder and ultrasonically dissolve it in 15mL of methanol to prepare a ligand solution. Then transfer the ligand methanol solution to a 100mL polytetrafluoroethylene reactor. Place the prepared alumina ceramic sheet deposited with zinc oxide nanosheets on a customized bracket with the nanosheets facing down, and then place the bracket in the reactor. The ligand steam heat treatment is carried out at 150°C. During this process, the ligand molecules can be uniformly produced under the action of methanol vapor, promoting the formation of the MOF membrane. After 6 hours of reaction, the membrane cleaning, pore activation and drying steps are the same as in Example 1.

[0065] Figure 8 and Fig. 9 The surface and cross-sectional SEM images and XRD patterns of the MOF membrane prepared by ligand steam-driven zinc oxide nanosheet conversion are shown. Different from the membrane prepared in Example 1, the steam thermal conversion of zinc oxide nanosheets produced a continuous and dense ZIF-L membrane with a thickness of about 4 μm. The ZIF-L membrane prepared by this method showed a high degree of compactness. The ZIF-L membrane showed excellent separation performance for carbon dioxide / nitrogen (CO2 / N2), with a permeability of about 300 GPU for carbon dioxide and a carbon dioxide / nitrogen separation selectivity of about 20.

[0066] Example 4

[0067] The preparation of zinc carbonate nanosheet layer is the same as that in Example 1.

[0068] 0.1 g of zinc carbonate nanosheets were dispersed in 50 mL of deionized water and deposited on the inner wall of a porous alumina ceramic tube (13 cm) by vacuum filtration to form a zinc carbonate nanosheet layer.

[0069] The alumina ceramic sheet deposited with the zinc carbonate nanosheet layer was calcined in a muffle furnace at 350° C. for 2 hours to form loosely stacked zinc oxide nanosheet layers.

[0070] Fig.10 It was demonstrated that a pure phase zinc oxide nanosheet layer with a thickness of ~2μm was formed on the inner wall of a porous alumina ceramic tube.

[0071] The outer surface of the alumina tube with a zinc oxide nanosheet layer deposited on the inner wall is sealed with a raw tape to prevent the ligand solution from penetrating into the support from the outside. Subsequently, the alumina tube is placed vertically in a polytetrafluoroethylene reactor filled with the ligand solution and subjected to solvent thermal reaction in a blast drying oven at 80°C for 6 hours. The ligand solution is prepared by dissolving 500mmol 2-methylimidazole in 200mL ethanol / water (1:2) mixed solvent. After the membrane conversion is completed, the membrane cleaning, pore activation and drying steps are the same as in Example 1.

[0072] Fig.11The surface and cross-sectional SEM images of the tubular ZIF-8 membrane prepared by conversion of zinc oxide nanosheets. It can be seen from the figure that the surface of the membrane is dense and defect-free, with a thickness of 3μm, and there is no pore permeation. The tubular ZIF-8 membrane exhibits excellent separation performance for propylene / propane (C3H6 / C3H8), with a permeation rate of about 100GPU for propylene and a separation selectivity of about 130 for propylene / propane.

[0073] Comparative Example 1

[0074] The method is basically the same as Example 1, except that zinc oxide sol is deposited on the surface of the alumina support instead of zinc carbonate nanosheets, and the zinc oxide sol is calcined at 350°C for 2 hours to obtain a dense zinc oxide layer (thickness of ~1 μm), which is then used as a zinc source to perform the same MOF film growth steps as in Example 1. Fig.12 The SEM image shows that the support body has obvious pore permeation, and the zinc oxide particles are filled in the pores of the support body. The support body coated with the zinc oxide particle layer is placed in a ligand solution for conversion reaction. The obtained membrane is subjected to the same post-treatment steps as in Example 1 and is also used for propylene / propane separation performance test. The ZIF-8 membrane ( Figure 2 ) is obviously different from the ZIF-8 membrane prepared by using the zinc oxide nanoparticle layer after ligand treatment for 6 hours in Comparative Example 1, which still has the characteristic peak of zinc oxide, indicating that the zinc oxide particles have not been completely converted ( Fig.13 ). Fig.14 The surface structure of the prepared ZIF-8 membrane is similar to that of Example 1, but the cross section is obviously different, and there is obvious ZIF-8 pore permeation phenomenon. The actual thickness of the membrane layer increased invisibly, resulting in an increase in mass transfer resistance. Therefore, the permeation rate of the membrane to propylene is only 25GPU, and the selectivity of propylene / propane is about 60, indicating that there are a small amount of grain boundary defects in the membrane. The membrane performance and separation performance are both worse than those of Example 1.

[0075] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a MOF film, characterized in that: The preparation method comprises the following steps: 1) depositing zinc carbonate nanosheets on the surface of a porous support; 2) calcining the porous support to obtain a porous support with a zinc oxide nanosheet layer deposited on the surface; 3) converting the zinc oxide nanosheet layer into a MOF film in the presence of an organic ligand to obtain the MOF film.

2. The method for preparing a MOF film according to claim 1, characterized in that: In step 1), after the deposition, the thickness of the zinc carbonate nanosheets is 0.5 to 2 μm; and / or, in step 1), the deposition is achieved by vacuum filtering a dispersion of the zinc carbonate nanosheets on a porous support; preferably, the molar concentration of the zinc carbonate nanosheets in the dispersion is 0.04 to 0.2 mol·L -1 ; and / or, the dispersed phase of the dispersion is selected from a combination of one or more of water, methanol, ethanol, and acetone.

3. The method for preparing the MOF film according to claim 1, characterized in that: The preparation method further comprises the step of preparing zinc carbonate nanosheets by hydrothermal reaction using zinc oxide nanoparticles and sodium bicarbonate aqueous solution as raw materials; preferably, the particle size of the zinc oxide nanoparticles is 50-200 nm; and / or the molar ratio of the zinc oxide nanoparticles to sodium bicarbonate is 1:1-3; and / or the temperature of the hydrothermal reaction is 60-100° C.; and / or the time of the hydrothermal reaction is 2-5 h; and / or the lateral size of the zinc carbonate nanosheets is 1-10 μm and the thickness is 10-50 nm.

4. The method for preparing a MOF thin film according to claim 1, characterized in that: The preparation method further comprises a step of vacuum drying before the calcination; and / or, in step 2), the calcination temperature is 300-500° C.; and / or, in step 2), the calcination time is 2-3 hours; and / or, in step 2), the thickness of the zinc oxide nanosheet layer is 0.5-2 μm.

5. The method for preparing the MOF thin film according to claim 1, characterized in that: In step 3), the organic ligand is selected from a combination of one or more of imidazole, benzimidazole, 2-methylimidazole, 4,5-dichloroimidazole, 5-chlorobenzimidazole, 5-methylbenzimidazole and 2-aminobenzimidazole; and / or, the organic ligand exists in the form of a solution, and the concentration of the organic ligand in the solution is 1 to 3 mol / L; and / or, in step 3), a ligand regulator is also added, and the ligand regulator is selected from a combination of one or more of sodium formate, formic acid, acetic acid, and benzoic acid.

6. The method for preparing a MOF thin film according to claim 1, characterized in that: In step 3), the conversion method is selected from a combination of one or more of solution heat treatment, steam heat treatment, and electrochemical treatment.

7. The method for preparing a MOF thin film according to claim 1, characterized in that: The porous support is selected from porous alumina or porous silicon carbide; and / or the pore size of the porous support is 0.2 to 5 μm, and the porosity is 30 to 50%; and / or the porous support is selected from one of a wafer, a single-channel tube or a multi-channel tube.

8. The method for preparing a MOF thin film according to claim 1, characterized in that: The MOF is selected from one or more combinations of ZIF-7, ZIF-8, ZIF-62, ZIF-71, ZIF-95, and ZIF-302.

9. A MOF thin film prepared by the method for preparing a MOF thin film according to any one of claims 1 to 8.

10. Use of the MOF film according to claim 9 for gas separation.

11. The use according to claim 10, characterized in that: The gas is selected from the group consisting of carbon dioxide / methane, carbon dioxide / nitrogen, ethylene / ethane, propylene / propane, and separation of hexane isomers.

Citation Information

Patent Citations

  • Composite material for gas adsorption separation and preparation method thereof

    CN115920863A

  • Metal organic framework polytetrafluoroethylene composite structure and manufacturing method thereof

    CN117615838A

  • Azole metal organic framework material as well as preparation method and application thereof

    CN118165280A

  • Metal organic framework, composition including metal organic framework, membrane and gas separation membrane composed of the composition, method for producing metal organic framework, and carbon dioxide adsorbent

    JP2023147220A